Space for Listening: using a library unConference as an alternative method of communication - Matthew Murray; A.L. Carson (Journal of eScience Librarianship, 2018)
As part of the University of Nevada, Las Vegas (UNLV) “Top Tier” initiative, the University Libraries contributes to the development of campus infrastructure and services to support research data management (RDM) and data preservation. Positioning the Libraries within the UNLV community as both partner and site for this development, we organized a faculty-oriented Research Data Management unConference during UNLV’s Research Week. The unConference attracted researchers and high-level administration from across campus and provided a forum for engagement; it was also a means for the Libraries to learn about researcher needs related to RDM, identifying potential partners, problems, and areas of support. Bridging disciplinary silos, invited speakers from academic and administrative units gave short presentations on different aspects of data management, which were followed by in-depth discussions of participant-selected topics relevant to RDM. The unConference succeeded in creating a space for meaningful interaction, with participants expressing interest in ongoing dialogue around RDM facilitated by the Libraries. Furthermore, the interactions we facilitated and feedback we received helped inform the Libraries’ next steps as we move the RDM conversation forward. This paper outlines the process of organizing and facilitating an unconference, lessons learned regarding outreach and researcher engagement, and potential pitfalls to avoid for library staff seeking to diversify their information-gathering strategies. The substance of this article is based upon poster presentations at RDAP Summit 2018 and the ALA Annual Conference and Exhibition 2018 .